Es Krim Ekstrak Tempe Kacang Tunggak dan Pasta Ekstrak Umbi Porang sebagai Penstabil: The Quality of Ice Cream with Cowpea Tempeh Extract and Porang Tuber Extract Paste as Stabilizer - Siedharta, Alexander Ryu; Swasti, Yuliana Reni; Pranata, Franciscus Sinung (Amerta Nutrition, 2024)
Background: Ice cream contains a high saturated fat and uses commercial stabilizers which are detrimental to health. This study uses cowpea tempeh extract containing a low saturated fat and porang tuber extract paste as natural stabilizers. Objectives: To determinate the effect of adding cowpea tempeh extract as a substitute for water and porang tuber extract paste as a replacement for carboxymethyl cellulose (CMC) and super polymer (SP) on the ice cream characteristics. Methods: This study used a completely randomized design with four treatments based on the ratios amount of cowpea tempeh extract and porang tuber extract paste (%), 0:0 (K), 5:1 (A), 10:1.5 (B), and 15:2 (C). This study measured the protein content, fat content, solids content, sucrose content, total plate counts, Salmonella prevalence, melting rate, overrun and panelists' preference. Results: The result of the ice cream testing shows that the protein content is 4.35%-7.47%, the fat content 8.68%-9.84%, the total solids content 23.53%-30.75%, the sugar content (sucrose) 20.67%-20.87%, the overrun 70.67%-100%, the melting rate 1019 seconds-1207 seconds, and the compliance with Indonesia National Standard dealing with the total plate counts and the Salmonella prevalence. Conclusions: The best ice cream is obtained in the treatment C (15%:2%).